Harnessing Nigeria’s Blue Economy through Islamic Finance: Maqāṣid-Based Framework for Sustainable Development - Mijinyawa, Sadiq Ibrahim; Ahsan, Muhamad; Fitrianto, Achmad Room; Sedjati, Mangesti Waluyo; Danmaraya, Mubarak Aliyu (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2026)
Prologue: The blue economy has attracted increasing global attention as a strategic framework for achieving sustainable development, particularly in coastal and marine resource-rich countries. In Nigeria, however, the development of the blue economy remains constrained by weak institutional governance, environmental degradation, limited financial inclusion, and inadequate long-term investment mechanisms. Existing development approaches largely rely on conventional economic models that insufficiently address the ethical, social, and ecological dimensions of marine sustainability. Objective: This study aims to examine how Islamic economic principles can contribute to the development of a more sustainable, inclusive, and ethically grounded blue economy framework in Nigeria. Methods: The study employs a qualitative conceptual approach grounded in an extensive review of scholarly literature, policy documents, and institutional reports on the blue economy, Islamic economics, sustainable finance, and marine governance. An integrated analytical framework is developed, grounded in maqāṣid al-sharīʿah as the normative foundation, supported by Islamic financial and social finance instruments, such as blue sukuk and waqf. Results/Findings: The findings indicate that conventional financing mechanisms alone are insufficient to address the multidimensional challenges of Nigeria’s blue economy. The integration of maqāṣid al-sharīʿah provides an ethical and sustainability-oriented framework that aligns economic development with environmental stewardship and social welfare. Furthermore, blue sukuk has significant potential as a long-term financing instrument for marine infrastructure and environmental projects, while waqf contributes to community-based empowerment, enhanced coastal welfare, and inclusive economic participation. Contribution: This study contributes to the growing discourse on Islamic sustainable finance by proposing an integrated Islamic blue economy framework that combines ethical governance, environmental sustainability, and inclusive development. It also offers policy-relevant insights for governments, Islamic financial institutions, and development agencies seeking alternative financing models for sustainable marine economic transformation in emerging economies.